Speciation analysis and dynamic absorption characteristics of heavy metals and deleterious element during growing period of Chinese peony. Issue 14 (6th December 2019) - Nan, Guanjun; Guo, Liying; Gao, Yuqiong; Meng, Xianxin; Zhang, Lina; Song, Ning; Yang, Guangde
Abstract: The heavy metals and deleterious element (Pd, Cd, Cu, As, and Hg) in Chinese peony ( Paeonia lactiflora Pall.) were determined by Tessier's sequence extraction method. Pb mainly existed in carbonate fraction. The main fraction of Cd in different tissues and different month is quite different. Cu mainly exists as exchangeable carbonate fractions. Five forms of Hg all exist in leaf, stem, and root. The total absorbable fraction of Pd, Cd, Cu, As, and Hg was different in different tissues. The total content of heavy metals can migrate from different tissues and the content of different speciation of heavy metal also can change during the growing period of plants. The results showed that different parts of plants and different elements resulted in different distribution and mobility. Base on this, it is more scientific and reasonable to clarify the migration and enrichment and to analyses the speciation of heavy metals during growing period of plant medicine. It is more scientific and reasonable to clarify the migration and enrichment, and to analyses the speciation of heavy metals during growing period of plant medicine.